Vpliv zdravstvene vzgoje na prehrano osnovnošolca - Balaban, Marija (Obzornik zdravstvene nege, 2000)
The article presents the results of the research study on the impact of healtheducation on eating habits of primary school children; it presents basicmeaures of healthy nutrition and stresses the importance of several nutrients for human health. It presents the eating habits of adolescents, the role of the rhythm of feeding and "junk" food in the care of ones health. As well, the diseases and problems related to nutrition in an adolescent are presented. It deals with improper eating habits of the Slovenians, including primary school children, based on the data on the research of eating habits ofSlovenian primary school children from 1996. The empirical part of the studypresents the results of two inquiries on healthy nutrition and eating habits-one was performed on 93 schoolchildren from 6th and 7th grade, and the other performed on the some group after a lecture on healthy nutrition. The results show that children acquired knowledge from this area but they eating habits do not change to a significant degree.
Keywords: Anorexia nervosa; Body mass index; Bulimia; Child nutrition; food; Food habits; Health education; Nutrition assessment; osnovnošolci; Parents; prehrana; zdravstvena vzgoja